Development of an application framework using event sourcing with CQRS and DDD - Zima, Martin; Pecinovský, Rudolf, 1954-; Rais, Aziz Ahmad; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
The thesis develops a new software application framework with the use of event sourcing, command-query responsibility segregation and domain-driven design. First, it identifies typical application ar-chitectures used today and examines their weak spots. These discussed architectures are generally difficult to scale, integrate and test and their codebases are hard to maintain. In order to provide a better solution, the thesis thoroughly studies several emerging approaches to software design (event sourcing, command-query responsibility segregation and domain-driven design) and analyzes their potential in improvements of the old application architecture. The work discusses and proposes pos-sible approaches to their implementation. Consequently, an improved architecture for the new frame-work is specified. As a result, it delivers a complete software solution for writing enterprise server applications in C#/on .NET platform that are able to focus on the implementation of complex busi-ness domains and are able to deal with challenges of scalability, maintainability or integrations in service-oriented architectures. Finally, the author elaborates on the experience of using the frame-work in a real commercial software product.
Vedoucí práce: Rudolf Pecinovský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses